A study on knowledge of breast feeding and complementary feeding practices among mothers in a rural area, Tamil Nadu, India - Venugopal, Sivagamasundari; Arulparithi, C. S. (International Journal of Contemporary Pediatrics, 2018)
Background: Breast feeding, an effective tool in bringing down the mortality and morbidity of infants and under 5 children has major barrier in successful establishment due to lack of proper knowledge among expectant mothers, family members and inappropriate cultural practices. Objective of this study was to determine the knowledge regarding breast feeding practices among mothers having children less than 3 years of age attending Paediatric OPD of Karpagavinayaga Institute of Medical Sciences, Kanchipuram for medical illness from rural area. Methods: This study is a hospital based cross sectional study was conducted for a period of 5 months from September 2017 to January 2018 with pretested structured questionnaire. Results: In this present study 81.7% of mothers were well known about exclusive breast feeding. 68.7% of the mothers knew that colostrum should be given as first feed. In this study only, the knowledge about the demand feed was present in 37.4% of mothers. Knowledge about complementary feed was present in 82.6% of mothers. 54.8% of mothers had known about Prelacteal feeds. Conclusion: This study shows that adequate knowledge regarding breast feeding and complementary feeding should be provided to the mother during their antenatal, postnatal period and during vaccination which greatly reduces infant and under 5 mortality and morbidity.